To make an image: the graphic production of the magazine "O Cruzeiro" - Campos, Daniela Queiroz (Dialogos, 2016)
“O Cruzeiro” magazine enshrined in the Brazilian scene as one of the best known and mostly disseminated periodical the twentieth century. Having started its circulation in 1928, the renowned magazine remained on newsstands across the country until the year 1975. The graphic quality of the printed media was notorious, especially in its early decades of publication. This article discusses the graphic production of the magazine “O Cruzeiro” from the original pages of the journal. The reproducibility makes, marks and consolidates those texts and those images.